2015
DOI: 10.1080/10941665.2015.1025087
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Segmentation of Spa Users: A Study of Inbound Travelers to Hong Kong

Abstract: Based on the increasing popularity of the wellness/spa trend and the growing numbers of inbound tourists to Hong Kong, it is crucial for spa industry experts to understand the ever-changing desires of consumers. The study aims to identify the lifestyle dimensions of international spa visitors to Hong Kong and to profile each segment based on their sociodemographic and travel characteristics. The study adopts a quantitative approach to segmenting international spa visitors in Hong Kong by lifestyle. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 54 publications
1
16
0
1
Order By: Relevance
“…With the increasing awareness of the value of spa treatments, people began to attach importance to the commercial and economic value of hot springs, particularly the tourism industry, mainly for the behavior and demand characteristics of tourists [18], travel motivations [36,38,42,43], the geographical characteristics of customer marketing [15], as well as visitors' evaluation of spa experiences [44]. In addition to focusing on the value of hot spring resources, researchers later began to discuss the influencing factors of hot spring tourism development, such as hot spring hot brand [45], the coordinated development of the entire region's economy, and ecology at the external macro level [12,15,46,47], while other scholars studied the advantages and disadvantages of hot spring resorts with case analyses [12], focused on services and activities at hot spring destinations [48][49][50], and service quality and consumer preferences [15,22,35,48].…”
Section: Hot Springs Tourism Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…With the increasing awareness of the value of spa treatments, people began to attach importance to the commercial and economic value of hot springs, particularly the tourism industry, mainly for the behavior and demand characteristics of tourists [18], travel motivations [36,38,42,43], the geographical characteristics of customer marketing [15], as well as visitors' evaluation of spa experiences [44]. In addition to focusing on the value of hot spring resources, researchers later began to discuss the influencing factors of hot spring tourism development, such as hot spring hot brand [45], the coordinated development of the entire region's economy, and ecology at the external macro level [12,15,46,47], while other scholars studied the advantages and disadvantages of hot spring resorts with case analyses [12], focused on services and activities at hot spring destinations [48][49][50], and service quality and consumer preferences [15,22,35,48].…”
Section: Hot Springs Tourism Studiesmentioning
confidence: 99%
“…Hot Spring Quality It refers to the quality of hot springs such as the water quality, and water temperature [47].…”
Section: Facilitiesmentioning
confidence: 99%
“…Valentine [ 30 ] highlights the usefulness of natural remedies based on air, water, rest, and healthy diets as a key factor for visiting a spa. Similarly, other authors have found that customers decide to go to spas because they consider them useful for improving their health [ 31 , 32 , 33 ]. Some authors have also found that spas are considered a useful place for socializing and building relationships [ 7 , 31 ].…”
Section: Hypothesis Developmentmentioning
confidence: 84%
“…Huh, Lee, and Lee [ 53 ] identify a spa-goer market segment that they call “pleasure pursuers,” which is the largest segment in their study. Kucukusta and Denizci Guillet [ 32 ] also identify a segment of pleasure-oriented spa-goers. Han, Thuong, Kiatkawsin, Ryu, Kim, and Kim [ 54 ] use the emotional dimensions of pleasure and arousal in their study on customers’ intention to return to a spa hotel.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation